2014
DOI: 10.1002/zaac.201400515
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal/Solvothermal Crystal Growth: an Old but Adaptable Process

Abstract: Hydrothermal crystal growth can be described as a low temperature process under pressure using an aqueous solution as the solvent. The temperature gradient controls the transport phenomenon from the nutrient to the seeds. The solvothermal term is generally used when the solvent is a non‐aqueous solution. Different aspects will be particularly discussed: (a) The principle of hydrothermal/solvothermal crystal growth processes. (b) A brief history of the development of such processes. (c) The main factors involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…6.d). Finally, a parallel can be made between hydrothermal crystal growth [42] and hydrothermal sintering of -quartz [41] where the driving force is the temperature gradient and the local pressure gradient, respectively. In both cases, the alkaline medium strongly favors the dissolution step by increasing the rate of dissolution.…”
mentioning
confidence: 99%
“…6.d). Finally, a parallel can be made between hydrothermal crystal growth [42] and hydrothermal sintering of -quartz [41] where the driving force is the temperature gradient and the local pressure gradient, respectively. In both cases, the alkaline medium strongly favors the dissolution step by increasing the rate of dissolution.…”
mentioning
confidence: 99%
“…Hydrothermal/solvothermal Method: For transition metal phosphates, the general procedure of "hydrothermal/solvothermal" is to perform the designed chemical reactions in selected solvents in sealed vessels. [111,112] For instance, various types of cobalt phosphates (e.g., CoHPO 4 ·3H 2 O, [48] Co 11 (HPO 3 ) 8 (OH) 6 , [113] and Co 3 (PO 4 ) 2 [114,115] ), nickel phosphates (e.g., Ni 11 (HPO 3 ) 8 (OH) 6 , [116] VSB-5, [117,118] and Ni 2 P 2 O 7 [119] ), manganese phosphates (e.g., Mn 3 (PO 4 ) 2 [108,120] and MnPO 4 ·H 2 O [121] ), vanadyl phosphates (e.g., VOPO 4 ·2H 2 O, [122] ) and silver phosphates (e.g., Ag 3 PO 4 [123] ) have been reported. The hydrothermal/solvothermal processes have also been adopted to prepare bimetallic phosphate, such as Co-Ni pyrophosphates, [124] which have shown improved performances compared to the monometallic phosphates.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…Hydrothermal/solvothermal Method : For transition metal phosphates, the general procedure of “hydrothermal/solvothermal” is to perform the designed chemical reactions in selected solvents in sealed vessels . For instance, various types of cobalt phosphates (e.g., CoHPO 4 ·3H 2 O, Co 11 (HPO 3 ) 8 (OH) 6 , and Co 3 (PO 4 ) 2 ), nickel phosphates (e.g., Ni 11 (HPO 3 ) 8 (OH) 6 , VSB‐5, and Ni 2 P 2 O 7 ), manganese phosphates (e.g., Mn 3 (PO 4 ) 2 and MnPO 4 ·H 2 O), vanadyl phosphates (e.g., VOPO 4 ·2H 2 O,) and silver phosphates (e.g., Ag 3 PO 4 ) have been reported.…”
Section: Metal Phosphidesmentioning
confidence: 99%
“…Most of the published works found the direct relationship between the crystallinity and photoactivity in the CdS nanostructures [34,35]. However, in recent studies we have demonstrated [29,30] the best photoactivity results for CdS nanostructures obtained at low solvothermal temperatures, associated with the formation of small crystalline CdS structures with quantum confinement effect (QD).…”
Section: Introductionmentioning
confidence: 96%
“…Among the different existing methodologies of nanosynthesis [25][26][27][28], we have studied in detail the solvothermal method because it is a simple one-pot process performed at low temperature that allows the preparation of well-crystallized materials. This methodology allows the control of the physicochemical properties and nanmorphology through the modification of the syntheses parameters described by Demazeau et al [29]. Solvothermal synthesis is a versatile methodology that has been succesfully applied for the obtention of oxides, nitrides, phosphides and even heterostructures for different photocatalytic applications [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%